Doença crônica na infância: a rede e o apoio social na perspectiva da família - Araujo, Yana Balduino de (2012)
Chronic disease affects the normal development of children and also affects social relations within the family system. The social network may contribute to better cope with the disease of children in that provides support to the family throughout the trajectory experienced. The study aimed to investigate, in view of the family, network and social support as strategies for coping with chronic illness in childhood. This is a qualitative study conducted in a public hospital in Paraíba Federal period April to June 2011, through the use of the genogram, eco-map and semistructured interviews with seven family members of children with chronic diseases. The graphical tools were analyzed according to the structure and bonds, since interviews were followed in the steps of thematic analysis. The analysis of empirical material for the interviews possible to characterize these families and understand the social interactions that have unfolded in the course of the disease and the types of support that they received or were absent. The empirical category: network and social support of families in the trajectory of chronic illness in childhood, was built in the process and pointed to the deepening of the dimensions of social support, which constitutes the most diverse forms of network members to provide input the family can better cope with the child's illness. The social network of families facing chronic illness in children is heterogeneous, composed of different people / institutions, and social support provided by this network is significant, however, is not always continuous and consistent with the needs of families. In the early families reported receiving little information support and reinforcement by health professionals. The emotional and instrumental support was provided by family members. Adaptation to therapeutic attempts were made to restructure the family dynamics and social support was declining, in some cases, families faced the child's illness alone. In the chronic phase, severe changes concerning the residence of members of networks, associated with a lower availability of social support to families were identified. The periods of relapse cause the displacement of families seeking care in health services that mostly were not prepared to receive these families and to continue the treatment of children, managing the crisis effectively and less traumatic. In the home environment, the network was also disjointed and insufficient to support the family. It requires a commitment and strengthening the relationship between the members of the network so that the support offered to the family is suited to its demands, continuing the experiential process that experience and provider of social support, can encourage the face of adversity disease. The construction of the social network from the initial and maintenance throughout the trajectory experienced by the family, is directly influenced by the bond that is established in the relations among the members at each meeting of care. Ways to strengthen these ties need to be prepared, so you can awaken a spirit of solidarity and collaboration among the members of this network.